Breast imaging for non-radiologists - Durur Subaşı, Irmak (Erciyes University Faculty of Medicine, 2022)
Breast carcinoma is the most frequent malignant tumor among women worldwide, and the incidence is increasing in Turkey. Screening with imaging modalities can provide early and accurate identification, and result in a lower treatment burden. While mammography (MG) and ultrasonography (US) continue to be the principal imaging methods, breast magnetic resonance imaging (MRI) is a more advanced imaging tool. This narrative review examines imaging modalities (MG, US, and MRI), pathology, breast carcinoma screening, axilla and male breast cancer for specialists other than radiologists, such as residents and students.
Keywords: Breast; Breast Cancer; Diagnostic Ultrasound; Magnetic Resonance Imaging; Mammography